Protocol for a randomized controlled trial evaluating the effect of Hibiscus syriacus L. flower extract on sleep quality - Choi, Yujin; Park, Yu Hwa; Yang, Changsop; Kim, Do Hoon; Lee, Kye Wan; Lee, Mi Young (Frontiers in Nutrition, 2023)
Introduction: Hibiscus syriacus L. flower (HSF) is a food ingredient commonly used for tea, and previous animal studies have reported its sleep-promoting effect. This study aims to test the potential of HSF extract as functional food that improves sleep in humans. Methods and analysis: Eighty participants with sleep disturbances who meet the inclusion/exclusion criteria will be enrolled in this study. Since the effect of HSF extract on sleep is considered to be that of a functional food rather than a medicine, participants with severe insomnia will be excluded from the study. The enrolled participants will be randomly assigned to the HSF extract or placebo groups in a 1:1 ratio. The HSF extract and placebo capsules will look identical, and participants, investigators, and outcome assessors will be blinded to the allocation. Four capsules of HSF extract or placebo will be orally administered 30-60 min before bedtime for four weeks. The primary outcome of this study will be the change in the Pittsburgh Sleep Quality Index (PSQI) global score from the baseline after four weeks. The subjective and objective changes in the participants’ sleep will be evaluated using the Insomnia Severity Index (ISI), Epworth Sleep Scale (ESS), sleep diary, and polysomnography (PSG). The occurrence of adverse events will be closely monitored. Discussion: The results of this trial will provide data on the efficacy and safety of HSF extract in enhancing sleep quality. Based on the results, the potential of HSF extract as a functional food that improves sleep in humans will be evaluated, and the findings of the trial will be submitted to the Korean Ministry of Food and Drug Safety for consideration as a new functional ingredient that may help to improve sleep quality. Trial registration: Clinical Research Information Service: KCT0007314; Registered 19 May 2022, https://cris.nih.go.kr/cris/search/detailSearch.do/21497.